PROMOTING THE DEVELOPMENT OF IMPROVED CLEANING TECHNOLOGY (Journal of Science-Innovative Research in Uzbekistan, 2023)
Improving product quality and maintaining its quality indicators as a result of reducing the cost of cleaning machines and increasing their efficiency due to the introduction of improved technologies into production information about.